Molecular Identification and Susceptibility Pattern of Clinical Nocardia Species: Emergence of Nocardia crassostreae as an Agent of Invasive Nocardiosis. Issue 2 (2013) - Taj-Aldeen, Saad J; Deshmukh, Anand; Doiphode, Sanjay; Abdul Wahab, Atqah; Allangawi, Mona; AlMuzrkchi, Ahmed; Klaassen, Corné H; Meis, Jacques F
Abstract : BACKGROUND: Nocardia species are rare, opportunistic organisms that cause disease in both immunocompetent and immunocompromised individuals. OBJECTIVE: To investigate the clinical presentations of various Nocardia infections based on the 16S ribosomal RNA gene of the isolate, as well as related risk factors and susceptibility patterns to antimicrobial agents METHODS: Thirteen patients with a diagnosis of nocardiosis were included in the present study. Seven Nocardia species were identified by 16S ribosomal RNA. Susceptibility testing was performed using six antimicrobial agents. RESULTS: Five patients were immunocompromised, and eight were immunocompetent with predisposing factors including cystic fibrosis, tuberculosis and ophthalmic infections. Nocardia caused pulmonary infections in eight patients (61.5%), invasive systemic infections in three patients (23%) and local (ophthalmic) infections in two patients (15.4%). In the patients with pulmonary disease, nocardiosis was caused by six species ( Nocardia cyriacigeorgica, Nocardia otitidiscaviarum, Nocardia farcinica, Nocardia carnea, Nocardia testacea and Nocardia asiatica) . The seventh species identified in the present study was Nocardia crassostreae. DISCUSSION: N crassostreae is a multidrug-resistant organism that was reported to be an emerging human pathogen causing invasive nocardiosis in a patient with non-Hodgkin's lymphoma. N farcinica was isolated from blood in a patient with breast cancer. None of the Nocardia isolates were resistant to linezolid. One N otitidiscaviarum isolate was a multidrug-resistant organism. All patients in the present study were treated with the appropriate antibiotics and their condition resolved without further sequelae. CONCLUSIONS: The present study is the first report on N crassostreae as a human pathogen. The detection of multidrug-resistant species necessitate molecular identification and susceptibility testing, and should be performed for all Nocardia infections. Nocardiosis manifests various clinical features depending on the Nocardia species and underlying conditions.